Angled telescopic surgery, an approach for laryngeal diagnosis and surgery without suspension - Morgado, Plínio Ferreira; Abrahão, Márcio (São Paulo Medical Journal, 1999)
CONTEXT: Many methods have been used successfully for the diagnosis and treatment of laryngeal diseases. Microscopic and, recently, telescopic surgery represent the state of the art in endoscopic laryngeal surgery but drawbacks are possible during their application. To keep the suspension apparatus adequately positioned, excessive force is sometimes placed on the upper teeth and tongue with the laryngoscope tube causing damage. Complications in relation to the pharynx, larynx and cardiovascular system have also been reported. OBJECTIVE: In order to reduce complications resulting from the manipulation or stimulation of the upper aerodigestive tract and from torque forces on the upper teeth. We present a method of larynx surgery in which laryngeal suspension is not required. DESIGN: Technical report. TECHNIQUES: We have devised a fiber-optic telescope with its 40mm distal portion deviated 60 degrees from the direction of the proximal portion. This angle was taken by measuring patients immediately before standard microlaryngeal surgery was performed. The surgical instruments have the same angle as the telescope, in order to work on the larynx. This technique provides an image that is not limited by the distal aperture of the laryngoscope and has an advantage in that magnification and illumination may be provided by changing the distance of the lesion from the tip of the instrument. we have operated on four patients with laryngeal diseases and have had no complications as a result of this approach. We feel that this technique gives us the freedom to view the lesions better and helps to minimize the drawbacks caused by laryngeal suspension.